Reconceptualizing Assessment For Learning In Mathematics Education: A Systematic Literature Review Of Digital, Formative, And Student-Centered Practices - Melkior Wewe; I Gusti L. A Parwata; I Dewa A. M Budhyani; I Gede Ratnya (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2026)
Assessment for Learning (AfL) is an important approach in mathematics education because it uses assessment evidence to support learning, not only to measure achievement. In primary and secondary mathematics classrooms, AfL is increasingly connected with digital tools, formative feedback, and student-centered practices. This study aims to reconceptualize AfL in mathematics education at the primary and secondary levels through a systematic literature review focusing on digital, formative, and student-centered practices. This study employed a Systematic Literature Review (SLR) approach guided by PRISMA 2020. A total of 150 articles were identified, and after the selection, screening, and eligibility process, 10 articles were included in the final synthesis. The data were analyzed using thematic synthesis through coding, theme development, and analytical interpretation. The findings show that AfL in mathematics education has developed from conventional formative assessment into a more diagnostic, adaptive, and participatory assessment ecosystem. Three main themes emerged from the synthesis. First, digital assessment supports faster feedback, personalized learning evidence, and better documentation of students’ progress. Second, formative assessment emphasizes feedback quality, evidence interpretation, and instructional follow-up. Third, student-centered assessment strengthens AfL when students understand criteria, use feedback, reflect on learning, and regulate their improvement. This study concludes that effective AfL in mathematics education should be pedagogically formative, digitally supported, and activated through students’ active participation.